Question
upstudy study bank question image url

Check \[ \begin{array}{l}\text { Select the inverse of each function. } \\ \text { a. } f(x)=-3 x-12 \\ \text { A) } f^{-1}(x)=-3 x+36 \\ \text { B) } f^{-1}(x)=-\frac{1}{3} x-4 \\ \text { C) } f^{-1}(x)=-4 x-\frac{1}{3} \\ \text { D) } f^{-1}(x)=3 x+12\end{array} \]

Ask by Chandler Mcguire. in the United States
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The inverse function is \( f^{-1}(x) = -\frac{1}{3}x - 4 \), which corresponds to option B.

Solution

To find the inverse of the function \( f(x) = -3x - 12 \), we will follow these steps: 1. **Replace \( f(x) \) with \( y \)**: \[ y = -3x - 12 \] 2. **Swap \( x \) and \( y \)**: \[ x = -3y - 12 \] 3. **Solve for \( y \)**: - First, add 12 to both sides: \[ x + 12 = -3y \] - Next, divide by -3: \[ y = -\frac{1}{3}(x + 12) \] - Simplifying this gives: \[ y = -\frac{1}{3}x - 4 \] 4. **Write the inverse function**: \[ f^{-1}(x) = -\frac{1}{3}x - 4 \] Now, let's compare this result with the provided options: - A) \( f^{-1}(x) = -3x + 36 \) - B) \( f^{-1}(x) = -\frac{1}{3}x - 4 \) - C) \( f^{-1}(x) = -4x - \frac{1}{3} \) - D) \( f^{-1}(x) = 3x + 12 \) The correct inverse function is: \[ \boxed{B} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find the inverse of the function \( f(x) = -3x - 12 \), we start by swapping \( f(x) \) with \( y \): 1. Set \( y = -3x - 12 \). 2. Now, solve for \( x \): \[ y + 12 = -3x \implies x = -\frac{1}{3}(y + 12) \] Simplifying gives: \[ x = -\frac{1}{3}y - 4 \] 3. Now, replace \( y \) with \( x \) to express the inverse function: \[ f^{-1}(x) = -\frac{1}{3}x - 4 \] So the correct answer is option B) \( f^{-1}(x) = -\frac{1}{3}x - 4 \). To verify this inverse, we can check if \( f(f^{-1}(x)) = x \) and \( f^{-1}(f(x)) = x \) holds true: For \( f(f^{-1}(x)) \): 1. Substitute \( f^{-1}(x) \) into \( f \): \[ f(f^{-1}(x)) = f\left(-\frac{1}{3}x - 4\right) = -3\left(-\frac{1}{3}x - 4\right) - 12 = x + 12 - 12 = x \] For \( f^{-1}(f(x)) \): 1. Substitute \( f(x) \) into \( f^{-1} \): \[ f^{-1}(f(x)) = f^{-1}(-3x - 12) = -\frac{1}{3}(-3x - 12) - 4 = x + 4 - 4 = x \] Thus confirming that the inverse function is correctly derived!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy